2022
DOI: 10.1177/21582440221093042
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of the Effect of Content Marketing on Online Consumer Behavior

Abstract: Notwithstanding the body of research on the characteristics and benefits of content marketing as a digital marketing strategy, evidence of how online consumer behavior is affected by digital brand content remains inconclusive. The current state results from the scattered and fragmented literature about content marketing which impedes a full understanding of scientific results that confirm the effect of content marketing activities on online consumer behavior. The purpose of this scoping review was therefore to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Other empirical research has documented a positive relationship between digital content marketing and purchase intention (Ahmad & Ilkay, 2019;Du Plessis, 2022;Milhinhos, 2015); however, recent research has found the relationship to be insignificant (Malthouse, Calder, Kim, & Vandenbosch, 2016). including the relationship between content marketing and engagement (Lee et al, 2018;El Kedra et al, 2020).…”
Section: Customer Engagementmentioning
confidence: 99%
“…Other empirical research has documented a positive relationship between digital content marketing and purchase intention (Ahmad & Ilkay, 2019;Du Plessis, 2022;Milhinhos, 2015); however, recent research has found the relationship to be insignificant (Malthouse, Calder, Kim, & Vandenbosch, 2016). including the relationship between content marketing and engagement (Lee et al, 2018;El Kedra et al, 2020).…”
Section: Customer Engagementmentioning
confidence: 99%
“…Because the idea of content marketing (CM) changes based on context, it can be challenging to come up with a specific definition. CM is increasingly being adopted by marketers as a replacement for interruptive advertising (Zahay, 2014;Du Plessis, 2015). Content marketing is ideal as it uses unobtrusive pulling and not pushing techniques to attract consumers to brand content (Liu & Huang, 2015).…”
Section: Content Marketing Conceptmentioning
confidence: 99%
“…Marketing professionals develop and distribute brand stories online with the aim of getting the target audience more familiar with the brand (Brieger, 2013). Often, CM is perceived as being like storytelling, inbound marketing, native advertising, and publishing (Holliman & Rowley, 2014;Du Plessis, 2015).…”
Section: Content Marketing Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, contemporary consumer behavior is deeply influenced by a plethora of communication channels. These platforms prove instrumental in informing, educating, and fostering consumer trust, influencing decisions [25] to choose remanufactured goods. Employing user-friendly websites, consumers gain invaluable insights into the advantages, quality, and environmental benefits of utilizing remanufactured products, equipping them with the requisite information for informed purchasing [26].…”
Section: Hypothesis 1 (H1)mentioning
confidence: 99%